Cost‐effectiveness analysis of vaginal misoprostol versus dinoprostone pessary: A non‐inferiority large randomized controlled trial in France. Issue 2 (19th November 2021) - Mounie, Michael; Costa, Nadège; Gaudineau, Adrien; Molinier, Laurent; Vayssière, Christophe; Derumeaux, Hélène
Abstract: Objective: To assess the cost‐effectiveness of vaginal misoprostol (PGE1; 25 μg) compared with a slow‐release dinoprostone (PGE2) pessary (10 μg) for labor induction due to an unfavorable cervix at term. Methods: We used data from an open‐label multicenter, randomized non‐inferiority trial that recruited women for whom labor was induced for medical reasons. The incremental cost‐effectiveness ratio was assessed from the payer's perspective, with the focus on inpatient care costs and using the cesarean deliveries avoided (CDA) rate as the primary analysis and the rate of vaginal delivery within 24 h (VD24) as the secondary analysis. Results: Analyses were based on 790 women in each group. Differences between treatment arms were the mean cost per patient of €4410 and €4399, a CDA rate of 80.1% and 77.9% and a VD24 rate of 46.1% and 59.4% for dinoprostone and misoprostol, respectively. Dinoprostone is not cost‐effective according to the CDA rate and misoprostol was either a cost‐effective or a dominant strategy according to the VD24. Conclusion: Misoprostol and dinoprostone have equal cost management with mixed efficacy according to the clinical outcome used. Finally, misoprostol may be an attractive option for hospitals as the price is lower and it is easier to use. Trial registration: ClinicalTrials.gov: NCT01765881. URL: https://clinicaltrials.gov/ct2/show/NCT01765881 . ClinicalTrialRegistrer.eu: 2011–000933–35. URL: https://www.clinicaltrialsregister.eu/ctr‐search/trial/2011‐000933‐35/FR . Abstract : We have shown disparate cost‐effectiveness results between 25 μg vaginal misoprostol versus dinoprostone pessary according to the clinical outcome and the payer perspective.